Impaired adenosine pathways in HFpEF: insights into cardiorenal alterations and endothelial responses - Riemma, Maria Antonietta; Madonna, Gennaro; Mele, Elena; Conte, Elena; Telesca, Marialucia; De Palma, Giacomo; Kutryb-Zając, Barbara; Cicala, Carla; Imbrici, Paola; Liantonio, Antonella; De Angelis, Antonella; Urbanek, Konrad; et al. (Frontiers in Pharmacology, 2026)
IntroductionHeart failure with preserved ejection fraction (HFpEF) accounts for nearly half of all heart failure cases and lacks effective therapies. Key features of HFpEF include endothelial dysfunction, fibrosis, and oxidative stress. Adenosine signaling, regulated by enzymes and receptors, is critical for vascular homeostasis and inflammation, but its role in HFpEF remains poorly understood. Adenosine receptors are abundantly expressed in the heart and kidney, modulating vascular, fibrotic, and tubular processes. Dysregulation of adenosine pathways in either organ may drive hypertension, microvascular dysfunction, and maladaptive cardio-renal crosstalk, highlighting the need to investigate adenosine signaling as a combined multi-organ target.MethodsHFpEF was induced in Dahl salt-sensitive rats by high-salt diet. Cardiac structure, function, fibrosis, oxidative stress, cytokines, renal adenosine receptors and cardiac adenosine pathway components were assessed using echocardiography, histology, proteome profiling and Western blotting. Human cardiac microvascular endothelial cells were treated with endothelin-1 in the presence of selective A2A or A2B agonists, or adenosine deaminase (ADA) inhibition, and profibrotic/oxidative stress genes were analyzed by qPCR.ResultsHypertensive rats exhibited diastolic dysfunction with preserved systolic function, cardiac and renal fibrosis, oxidative/nitrative stress, and elevated pro-inflammatory cytokines. Cardiac expression of CD39, CD73, and ADA enzymes was significantly reduced, indicating impaired adenosine metabolism, while transporters ENT2 and CNT2 were also downregulated, reflecting impairment of both equilibrative and concentrative adenosine transport. Adenosine receptor profiles were altered: A1 expression increased, A2A decreased, and A2B and A3 selectively upregulated in hypertensive, but not HFpEF, animals. In the kidney, A1 and A2A receptor expression showed region-specific, time-dependent changes. In human endothelial cells, A2A activation or ADA inhibition suppressed endothelin-1-induced COL1, COL3, and TGF-β1 expression, whereas A2B had no effect. Both A2A and A2B restored MnSOD expression, while NOX4 was selectively increased by A2B. Only A2A activation induced CAT expression, highlighting its stronger antioxidant role.ConclusionImpaired adenosine metabolism and transport, along with altered receptor signaling contribute to HFpEF progression. Selective A2A activation attenuates endothelial pro-fibrotic profiles and restores antioxidant defenses, supporting its therapeutic potential. Renal receptor changes reinforce maladaptive cardio-renal crosstalk, emphasizing the importance of multi-organ adenosine modulation in HFpEF and encouraging further translational studies.